2013
DOI: 10.1017/s1743921313015986
|View full text |Cite
|
Sign up to set email alerts
|

Polyynyl-Substituted PAH Molecules and DIB Carriers

Abstract: Abstract. Polycyclic aromatic hydrocarbon (PAH) molecules have been long considered promising candidates for the carriers of the diffuse interstellar bands (DIBs). The PAH-DIB hypothesis, however, raises two major issues. First, the number of interstellar PAH species is potentially orders of magnitude larger than the number of DIBs. Second, the absorption spectrum of a PAH is in general dominated by bands found at UV wavelengths while, conversely, DIBs are absent from the UV wavelength domain and arise at visi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…They found that while a regular PAH would survive in H I regions, its substituted counterparts would undergo fragmentation in the same UV radiation field. This could suggest that the ethynyl derivatives would not survive in H I regions, in contrast with our expectation that they are photostable (Rouillé et al 2012(Rouillé et al , 2013.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…They found that while a regular PAH would survive in H I regions, its substituted counterparts would undergo fragmentation in the same UV radiation field. This could suggest that the ethynyl derivatives would not survive in H I regions, in contrast with our expectation that they are photostable (Rouillé et al 2012(Rouillé et al , 2013.…”
Section: Introductioncontrasting
confidence: 82%
“…In previous works, we measured the UV/vis absorption bands of C 2 H-and C 4 H-substituted species isolated in Ne matrices. The spectra led us to propose photostable substituted PAH molecules, or similar species, as valid candidates for the carriers of the DIBs (Rouillé et al 2012(Rouillé et al , 2013. It was indeed observed that the addition of an acetylenic side chain to a regular PAH lowers the peak intensity and broadens the profile of the strong absorption bands that these species typically show at UV wavelengths (the β-bands), where DIBs are not observed (Clayton et al 2003;Gredel et al 2011;Salama et al 2011;Bhatt & Cami 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We also recorded the IR spectra of these compounds embedded in CsI pellets . Subsequently, we measured the UV/Vis spectrum of Ne matrix‐isolated 9,10‐diethynylanthracene . These studies prompted us to investigate butadiynyl‐ and hexatriynyl‐substituted PAHs by reversed‐phase high‐performance liquid chromatography (RP‐HPLC) for the determination of their experimental retention data.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Subsequently,w em easured the UV/Vis spectrum of Ne matrix-isolated9 ,10-diethynylanthracene. [8] These studies prompted us to investigate butadiynyl-and hexatriynyl-substituted PAHs by reversed-phase high-performance liquid chromatography (RP-HPLC) for the determination of their experimental retention data. Our experimental data are useful for the identification of these compounds in samples analyzed by RP-HPLC and offer the possibility to establishq uantitative structure-retention relationships( QSRRs).…”
Section: Introductionmentioning
confidence: 99%